Dates Palm Increases Breast Milk Production of Breastfeeding Mothers - Handayani; Mar’atus Sholichah Fitriah Hajar Kusnianto; Wahyu Wibisono; Entan Afriannisyah (Journal of Ners and Midwifery, 2024)
Breastfeeding is the ideal step in providing breast milk that is good for newborns and babies. Good support and effort can influence success in the breastfeeding process. Breast milk production is the key to breastfeeding and baby health. This study aimed to analyze the effectiveness of dates palm in increasing breast milk production of breastfeeding mothers. This study used secondary data, which was searched through the Google Scholar and Research Gate databases, to discuss the effect of dates palm on breastfeeding mothers for breast milk production. The study design of this research was a Systematic Literature Review. The research results showed 2 research articles that met the criteria which stated that there was an effect of dates on breastfeeding mothers to increase breast milk production. The researchers concluded that dates palm can be considered as an alternative to increase breast milk production in breastfeeding mothers. Dates palm are safe for consumption by breastfeeding mothers and pregnant women. This research is expected to be a form of meta-analysis by adding more similar articles to update the results of the effect of giving dates palm on breast milk production.